2022
DOI: 10.1214/21-ejp706
|View full text |Cite
|
Sign up to set email alerts
|

Hausdorff dimensions for shared endpoints of disjoint geodesics in the directed landscape

Abstract: Within the Kardar-Parisi-Zhang universality class, the space-time Airy sheet is conjectured to be the canonical scaling limit for last passage percolation models. In recent work [27] of Dauvergne, Ortmann, and Virág, this object was constructed and, upon a parabolic correction, shown to be the limit of one such model: Brownian last passage percolation. The limit object without parabolic correction, called the directed landscape, admits geodesic paths between any two space-time points (x, s) and (y, t) with s <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 50 publications
(75 reference statements)
0
16
0
Order By: Relevance
“…The set of exceptional pairs of points between which there is a non-unique geodesic in the directed landscape L was studied in [BGH22]. Their approach relied on [BGH21] which studied the random nondecreasing function z → L(y, s; z, t) − L(x, s; z, t) for fixed x < y and s < t. This process is locally constant except on an exceptional set of Hausdorff dimension 1 2 .…”
Section: Semi-infinite Geodesics and Busemann Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The set of exceptional pairs of points between which there is a non-unique geodesic in the directed landscape L was studied in [BGH22]. Their approach relied on [BGH21] which studied the random nondecreasing function z → L(y, s; z, t) − L(x, s; z, t) for fixed x < y and s < t. This process is locally constant except on an exceptional set of Hausdorff dimension 1 2 .…”
Section: Semi-infinite Geodesics and Busemann Functionsmentioning
confidence: 99%
“…Their approach relied on [BGH21] which studied the random nondecreasing function z → L(y, s; z, t) − L(x, s; z, t) for fixed x < y and s < t. This process is locally constant except on an exceptional set of Hausdorff dimension 1 2 . From here [BGH22] showed that for fixed s < t and x < y, the set of z ∈ R such that there exist disjoint geodesics from (x, s) to (z, t) and from (y, s) to (z, t) is exactly the set of local variation of the function z → L(x, s; z, t) − L(y, s; z, t), and therefore has Hausdorff dimension 1 2 . Going further, they showed that for fixed s < t, the set of pairs (x, y) ∈ R 2 such that there exist two disjoint geodesics from (x, s) to (y, t) also has Hausdorff dimension 1 2 , almost surely.…”
Section: Semi-infinite Geodesics and Busemann Functionsmentioning
confidence: 99%
“…Geodesics of L have properties that hold almost surely in the underlying randomness, some of which are listed below as they will be used throughout our discussion. These are derived from [3,9,10].…”
Section: Geodesics and Their Propertiesmentioning
confidence: 99%
“…For every compact subset K ⊂ R 2 , there is an > 0 such that if g and g are two geodesics whose graphs lie in K and are within distance , then there is a common time t such that g(t) = g (t). See [3,Theorem 1.18].…”
Section: Nearby Geodesics Meetmentioning
confidence: 99%
“…This paper and [CHHM21] are also not the first to study fractal geometry in a KPZ limit. For example, [BGH21,BGH22] use Brownian absolute continuity results to study fractal geometry in the directed landscape. One major difference between the problem studied here and in [CHHM21] and those previous works is that here, we are trying to understand what happens as the time coordinate changes.…”
Section: Introductionmentioning
confidence: 99%